Small printed UWB monopole antenna - Abbak, Mehmet; Büyükyavuz, Mehmet Can; Şimşek, Serkan (IEEE, 2012)
A compact microstrip-fed ultra-wideband monopole antenna is presented. The antenna has a simple planar structure and occupies a compact size of 22mm × 16mm × 1mm, including the feeding mechanism. Proposed antenna, which is printed on FR4 substrate with a relative permittivity of 4.4 has been easily fabricated and has low manufacturing cost, has a bandwidth from 3.8 GHz to 12 GHz, and has a stable omni directional pattern at x-z plane over the frequency band. In antenna design, we simulate and investigate this antenna structure by using finite element method (FEM) based Ansoft's HFSS program.